Are the classic diagnostic methods in mycology still state of the art?. (May 2016) - Wiegand, Cornelia; Bauer, Andrea; Brasch, Jochen; Nenoff, Pietro; Schaller, Martin; Mayser, Peter; Hipler, Uta‐Christina; Elsner, Peter
Summary: The diagnostic workup of cutaneous fungal infections is traditionally based on microscopic KOH preparations as well as culturing of the causative organism from sample material. Another possible option is the detection of fungal elements by dermatohistology. If performed correctly, these methods are generally suitable for the diagnosis of mycoses. However, the advent of personalized medicine and the tasks arising therefrom require new procedures marked by simplicity, specificity, and swiftness. The additional use of DNA‐based molecular techniques further enhances sensitivity and diagnostic specificity, and reduces the diagnostic interval to 24–48 hours, compared to weeks required for conventional mycological methods. Given the steady evolution in the field of personalized medicine, simple analytical PCR‐based systems are conceivable, which allow for instant diagnosis of dermatophytes in the dermatology office (point‐of‐care tests).